Menggali nilai karakter dalam ungkapan hikmah di sekolah dasar se-Karesidenan Surakarta - Dini Restiyanti Pratiwi; Eko Purnomo; Agus Budi Wahyudi; Muhamad Fakhrur Saifudin (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2021)
The phrase Wisdom that can be abbreviated (UH) is a summary that is pasted on the walls of the elementary school. The presence of language in UH is interesting to study and the results can be used in the field of education. This study has a goal, namely (1) to determine the form of expression of wisdom in SD Se-Residency Surakarta, (2) to find the values of character education that exist in the expression of wisdom. The type of research used is qualitative by using descriptive methods in describing the data found. The data in this study is UH which contains the value of character education. While the data sources used are sentences in UH on the walls of elementary schools in the Surakarta Residency area (Surakarta, Karanganyar, Sragen, Boyolali, Klaten, and Wonogiri). Data collection techniques used are observation, documentation, and note-taking techniques. The data analysis used were FGD, the distribution method with the Indirect Sharing (BUL) technique, and the matching technique with referential advanced techniques. For data validation used theory triangulation. The results of this study indicate that the UH at SD Se-Residency Surakarata contains 18 values of character education (religious, honest, democratic, tolerance, discipline, hard work, creative, independent, likes to read, cares about the environment, social care, curiosity). , love for the homeland, responsibility, national spirit, respect for achievement, friendly/communicative, and love peace)..